Changes in verbal learning and memory in schizophrenia and non-psychotic controls in midlife: A nine-year follow-up in the Northern Finland Birth Cohort study 1966. Issue 3 (30th August 2015) - Rannikko, Irina; Haapea, Marianne; Miettunen, Jouko; Veijola, Juha; Murray, Graham K.; Barnett, Jennifer H.; Husa, Anja P.; Jones, Peter B.; Isohanni, Matti; Jääskeläinen, Erika
Abstract: Findings on longitudinal change of cognitive performance in schizophrenia are extremely variable in the case of verbal learning and memory, and it is still unclear which dimensions of verbal learning and memory exhibit possible deterioration over the long-term. Our aim was to compare the change in verbal learning and memory in individuals with schizophrenia 10–20 years after the illness onset and healthy controls during a nine-year follow-up in a general population sample. Our sample included 41 schizophrenia spectrum subjects and 73 controls from the Northern Finland Birth Cohort study 1966. The California Verbal Learning Test (CVLT) was used to estimate the degree of change in verbal learning and memory during a nine-year follow-up from age 34-years to 43- years. Both cases and controls deteriorated. There was statistically significant decline in two out of 20 CVLT items among cases and in 13 out of 20 CVLT items among controls. With the exception of two variables, the decline in verbal learning and memory over nine years was not significantly larger in cases. We conclude that during midlife verbal learning and memory in schizophrenia mostly declines in a normative fashion with aging at the same rate as the general population. Highlights: Cases had lower cognitive performance than controls cross-sectionally. Both cases and controls declined in cognitive performance in 9-year follow-up. There was statistically significant decline in 2/20 CVLT items among cases. There was statistically significant decline in 13/20 CVLT items among controls. There mainly was no difference in the magnitude of decline in cases and controls.